Fluidized Beds for Concentrated Solar Thermal Technologies—A Review - Tregambi, Claudio; Troiano, Maurizio; Montagnaro, Fabio; Solimene, Roberto; Salatino, Piero (Frontiers in Energy Research, 2021)
Thermal and thermochemical processes can be efficiently developed and carried out in fluidized beds, due to the unique properties of fluidized suspensions of solid particles and to the inherent flexibility of fluidized bed design and operation. Coupling fluidization with concentrated solar power is a stimulating cross-disciplinary field of investigation, with the related issues and opportunities to explore. In this review article the current and perspective applications of fluidized beds to collection, storage and exploitation of solar radiation are surveyed. Novel and “creative” designs of fluidized bed solar receivers/reactors are reported and critically discussed. The vast field of applications of solar-driven fluidized bed processes, from energy conversion with thermal energy storage, to solids looping for thermochemical energy storage, production of fuels, chemicals and materials, is explored with an eye at past and current developments and an outlook of future perspectives.